The Influence Of One Thousand And One Nights On Chinese Folklore/ تأثير ألف ليلة وليلة على الحكاية الشعبية الصينية - Lei, Yang; Osman, Rahmah Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to examine the influence of One Thousand and One Nights on Chinese folk tales, with a focus on the literary and cultural relationship between the Arab and Chinese heritages during the Tang Dynasty period (700 CE–907 CE). The research problem arises from the scarcity of studies addressing this influence, especially in the literature of Chinese minorities impacted by One Thousand and One Nights. The study seeks to answer several key questions, including defining One Thousand and One Nights and Chinese folk tales, exploring how One Thousand and One Nights influenced this type of literature, and analyzing the objective and subjective factors that contributed to this influence, with particular attention to three Chinese folk tales influenced by One Thousand and One Nights. To achieve these objectives, the researcher employs two primary methodologies: the descriptive method, to illustrate the influence of three tales from One Thousand and One Nights on three Chinese folk tales by highlighting their content, and the analytical method, to examine the factors contributing to this influence and reveal the literary background of both Arab and Chinese traditions during that era.